KARAKTER PROTAGONIS PANCHITO: STUDI CERPEN THE CIRCUIT KARYA FRANCISCO JIMÉNEZ - Kustinah Kustinah; Didik Rinan Sumekto (Universitas Muhammadiyah Surakarta, 2021)
The short story of The Circuit substantially carries on the American Dream from the immigrants’ expectations living in California. Their expectations rely on spirituality, wealthy, freedom, and other life necessity aspects. This research reviewsthe protagonist character as written in Francisco Jiménez’s The Circuit and applies for the content analysis method. Data collection primarily uses the short story of Jiménez’s The Circuit as part of the philology research. Data analysis deals with the intrepretative approach by identifying and mapping the life of a migrant child in 1947 documented in The Circuit facts. The findings showed that the protagonist characters tightly correspond with the life of a-4-year-old Panchito, who is conditionally forced to work with his parents as the nomad fruit picker in the entirely ready-harvesting plantation areas of California Federal State with a very low wage granted and dwell in inappropriate housing. Panchito’s protagonist character addresses a positive and tough motivation in happening his dreams that trigger the expansive morality values toward life struggles. Keywords: mexican immigrants, life struggle, protagonist, Panchito